POLITIK HUKUM TELEMEDICINE INDONESIA: ANTARA PEMERATAAN AKSES LAYANAN KESEHATAN DENGAN PERLINDUNGAN HUKUM BAGI PASIEN DAN TENAGA MEDIS - Rambe, Muhammad Juang; Risdawati, Irsyam; Siregar, Elza Anggraini (Scenario (Seminar of Social Sciences Engineering and Humaniora); 2023, 2023)
According to data from BPS Prov. North Sumatra, health services through telemedicine are considered a solution to overcome the problem of inequality of medical personnel, especially doctors and specialists, in the region. However, there are several legal issues that hinder the implementation of telemedicine in providing equitable access to health. Therefore, it is expected that the government will take immediate action to establish more comprehensive arrangements in laws related to public health services in order to meet current needs, such as Law No. 29/2004 on Medical Practice, Law No. 36/2009 on Health, and Law No. 44/2009 on Hospitals. The adjustment of these laws shows the need to regulate telemedicine in a law that considers the interests and safety of patients and protection for medical and health personnel. In addition to providing convenience for patients in accessing health services, this telemedicine regulation must provide clear guidelines and legal certainty for medical and health personnel while maintaining service quality. Some of the existing materials in the telemedicine instrument are still relevant but need to be adjusted to the new instruments that will be formed, such as telemedicine organizers. Keywords: Politics, Law, Telemedicine, Health Services.